Phenotypic and molecular detection of biofilm formation in clinical methicillin-resistant Staphylococcus aureus isolates from Malaysia - Sherry Usun Jones; Boon Pin Kee; Ching Hoong Chew; Chew Chieng Yeo; Fatimah Haslina Abdullah; Norlela Othman; Kek Heng Chua; Suat Moi Puah (Journal of Taibah University for Science, 2022)
ABSTRACTMethicillin-resistant Staphylococcus aureus (MRSA) is among the top threats to global public health and biofilm production is one of the factors attributed to its pathogenesis. This study aims to investigate the biofilm forming ability of 89 clinical MRSA isolated from various sources in Malaysia and to investigate the presence of biofilm-associated and regulatory genes among these isolates. A total of 89.9% (80/89) isolates produced slime layer via Congo red assay while 57.3% (51/89) isolates produced strong biofilm via crystal violet assay. PCR assay revealed 97.8% (87/89) isolates carried at least one of the MSCRAMM with icaBC genes detected at the highest rate (92.1%, 82/89) and highest frequency of agr-I (68.5%, 61/89). Clinical isolates isolated from pus were significantly associated with strong biofilm (p = 0.0449). The obtained results revealed the varying ability of clinical MRSA isolates to form biofilms and highlighted the genetic background associated with biofilms from different sources and clinical presentations.